Intelligence, Self-confidence and Entrepreneurship - Andrea Asoni (Research Institute of Industrial Economics (IFN), 2011)
I investigate the effect of human capital on entrepreneurship using the National Longitudinal Survey of Youth - 1979. I find that individuals with higher measured intelligence and self-confidence are more likely to be entrepreneurs. Furthermore I present evidence suggesting that intelligence and self-confidence affect business ownership through two different channels: intelligence increases business survival while self-confidence increases business creation. Finally, once we control for intelligence and self-confidence the effect of formal college education almost completely vanishes. These results are robust to controlling for selection into entrepreneurship and selection into college.
Keywords: C41; J24; L26; 330; Entrepreneurship; College Education; Intelligence; Self-confidence; Humankapital; Intelligenz; Persönlichkeitspsychologie; Unternehmer; Unternehmensgründung; USA